Optimization of structures under buckling constraints using frame elements. Issue 1 (2nd January 2019) - Mitjana, Florian; Cafieri, Sonia; Bugarin, Florian; Gogu, Christian; Castanie, Fabien
ABSTRACT: Structural optimization is of increasing interest in a wide variety of application fields. In this article, structural optimization under stress and buckling constraints is investigated. A structure comprised of a set of frame elements is considered. The aim is to obtain the minimal mass structure, by optimizing the number of frame elements and their cross sectional dimensions. A formulation as a mixed-integer nonlinear optimization problem with a tailored objective function is introduced. This cost function is a combination of the structural mass and the sum of the second moments of inertia of each structural element. Moreover, a new algorithm, tailored to the considered problem, is proposed. Numerical results show that the proposed approach provides interesting structural mass savings.